Capital Markets Union: The Need for Common Laws and Common Supervision - Jan Friedrich; Matthias Thiemann (Vierteljahrshefte zur Wirtschaftsforschung, 2017)
This paper examines the supervision of Central Clearing Counterparties (CCPs) in Europe, since they function as an important pillar of the Capital Markets Union. Our research indicates that the current national-based supervision of CCPs leads to regulatory arbitrage and exposes the EU to huge financial risks, especially in the context of the Brexit. We claim that a unified capital market should have a centralized capital markets regulator to avoid a hazardous regulatory race to the bottom. We argue that the ECB is suitable for taking on this common supervisor role in the short run, while ESMA should be equipped with enhanced capabilities to accomplish the task in the long run. – – Dieser Artikel analysiert die Aufsicht von central clearing counterparties (CCPs) in Europa, da diese einen wichtigen Eckpfeiler der Kapitalmarktunion darstellen. Unsere Forschung deutet darauf hin, dass die derzeitige nationale Organisation der Aufsicht von CCPs zu regulatorischer Arbitrage führt und die EU einem erheblichen finanziellen Risiko aussetzt, insbesondere vor dem Hintergrund des Brexit. Wir fordern, dass ein einheitlicher Kapitalmarkt auch einen zentralen Kapitalmarktaufseher haben sollte, um ein gefährliches regulatorisches race-to-the-bottom zu verhindern. Wir argumentieren, dass die ECB kurzfristig ein geeigneter zentraler Aufseher ist, während ESMA langfristig mit erweiterten Kompetenzen ausgestattet werden sollte um diese Aufgabe zu übernehmen.
Keywords: G18; G23; K22; 330; Capital Markets Union; clearing; regulatory competition; regulatory arbitrage; supervision